World Economic Outlook, October 2014 : Legacies, Clouds, Uncertainties. (World Economic Outlook; World Economic Outlook ;, 2015)
The pace of recovery has disappointed in recent years, and downside risks have increased, including from heightened geopolitical tensions. These increased risks make it a priority to raise actual and potential growth. In a number of economies, an increase in public infrastructure investment can also provide support to demand and help boost potential output. And in advanced economies as well as emerging and developing economies there is a general, urgent need for structural reforms to strengthen growth potential or make growth more sustainable. The four individual chapters examine the overall global outlook, the prospects for individual countries and regions, the benefits of increased public infrastructure investment in terms of raising output, and the extent to which global imbalances have narrowed significantly since their peak in 2006.